2003
DOI: 10.1038/sj.hdy.6800349
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity of nuclear and mitochondrial genomes in Pinus parviflora Sieb. & Zucc. (Pinaceae) populations

Abstract: Genetic diversities of the nuclear and mitochondrial genomes in Pinus parviflora were studied in 16 populations, which were distributed across most of the species' range in Japan. Six mitochondrial DNA haplotypes were identified among the 16 populations. The intrapopulation diversity of allozymes was similar to that of other endemic woody species (H S ¼ 0.259). Although P. parviflora is distributed in discrete populations, differentiation between these was very low (G ST ¼ 0.044). In addition, the extent of ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 40 publications
1
19
0
Order By: Relevance
“…parviflora. Two haplotypes dominated northern Japan and the JS, while other two types dominated western Japan and the PO (Tani et al 2003). These authors also found that the distribution of mitochondrial haplotypes reflected taxonomic differences between the two varieties.…”
Section: Review Of Plant Phylogeography In Japanmentioning
confidence: 48%
See 4 more Smart Citations
“…parviflora. Two haplotypes dominated northern Japan and the JS, while other two types dominated western Japan and the PO (Tani et al 2003). These authors also found that the distribution of mitochondrial haplotypes reflected taxonomic differences between the two varieties.…”
Section: Review Of Plant Phylogeography In Japanmentioning
confidence: 48%
“…These authors found four Fig. 2 Examples of the distribution of intra-and inter-population genetic variation in alpine and sub-alpine (left side) and montane (right side) plant species in the Japanese Archipelago, redrawn from the following studies with permission from the Genetics Society of America, Macmillan Publishers Ltd., and Wiley-Blackwell Publishers; Cardamine nipponica (Ikeda et al 2008a), Picea alcoquiana (Aizawa et al 2008), Picea jezoensis (Aizawa et al 2009), Pinus parviflora (Tani et al 2003), Betula maximowicziana (Tsuda and Ide 2005), Cryptomeria japonica (Tsumura et al 2007a), Fraxinus mandshurica var. (Hu et al 2010), and Quercus crispula (Ohsawa et al 2011).…”
Section: Review Of Plant Phylogeography In Japanmentioning
confidence: 99%
See 3 more Smart Citations